Vermicompost and vermiwash as supplement to improve seedling, plant growth and yield in Linum usitassimum L. for organic agriculture - Cinny Makkar; Jaswinder Singh; Chander Parkash (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose To study the organic production in two varieties of Linum (Linseed) crop using different proportions of vermicomposts and combination of vermiwash as an environment friendly substitute to chemical fertilizers for organic farming of Linseed. Method Vermicompost prepared from cattle dung was mixed in different proportions, i.e. 0, 20, 40, 60, 80, and 100% vermicompost v/v with soil and commercial potting media (Perlite, Peat and Coconut coir). To study the germination, vegetative growth, reproductive growth and yield in two varieties of Linum usitassimum L. LC-54 and LC-2063 were grown in a polyhouse for a 2 years trial. A total of 960 seedlings and 240 plants were studied for assessment of result in 24 treatments. Additional treatments with foliar application of 1:1 v/v vermiwash and recommended dose of inorganic fertilizer were done to determine and compare the role of vermicompost, vermiwash and inorganic treatment. Results Substituting soil with 60% (v/v) vermicompost in LC-54 and with 40% (v/v) vermicompost in LC-2063 improved the performance of seeds, root morphology and stem growth. Life cycle of crop was shortened in two varieties of Linseed raised under different treatments of vermicompost and vermiwash. Performance of LC-54 was better at 60% and that of LC-2063 was at 40%, which can be attributed to their genotypic differences. Vermicompost proportion above 60% was of no use at any stage of life cycle in both the varieties of Linum. Germination and yield were further improved when foliar application of vermiwash was integrated with vermicompost for nutrient management when compared with recommended chemical fertilizer treatment and control. Conclusion Bio-efficacy of vermicompost and vermiwash for production of organic Linseed crop has been well established with enhanced yield.